Implementation of Public Policy on Health Services Based on Law Number 23 of 2014 on Regional Government - Ni Putu Sawitri Nandari; Bagus Gede Ari Rama; Dewa Krisna Prasada; Putu Suparna (Fakultas Hukum, Universitas Warmadewa, 2025)
Regional autonomy is the right, authority, and obligation of autonomous regions to regulate and manage their own Government Affairs and the interests of the local community in the Unitary State of the Republic of Indonesia (NKRI) system. The type of research used is normative or doctrinal law, through qualitative descriptive legal analysis. Results and discussion of the implementation of public policy on health services based on Law No. 23 of 2014 concerning Regional Government, namely health services are part of concurrent government affairs because health services are the authority of the Regional Government based on the principle of decentralization, so the regional government has the right to manage all forms of health service provisions, as regulated in Article 12 paragraph (1) which states that government affairs must provide basic services, one of which is in terms of health. The Bali Provincial Government is developing services in terms of traditional health by issuing Governor Regulation No. 55 of 2019 concerning Traditional Balinese Health Services. The Central Government and Regional Government are required to coordinate, especially in making regulations so that they have a socially just impact on all Indonesian people, especially in the field of health services that must reach remote villages. Health service efforts are carried out in a promotive, preventive, curative and rehabilitative manner carried out by the government.